New species and records of Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) in continental China - Wang, Dan; Yin, Zi-Wei (Zootaxa, 2016)
Nine new species of the genus Batraxis Reitter are described from continental China: Batraxis robusta sp. n., B. gloriosa sp. n., B. antennata sp. n., B. longicornis sp. n., B. gesar sp. n., B. longithorax sp. n., B. nanlingensis sp. n., B. yifan sp. n., and B. ziyueae sp. n. New records of B. bicolor Wang & Yin and B. tibialis Wang & Yin are given. An identification key to the Batraxis species of China based on males is provided.